The advocacy continuum: Towards a theory of advocacy in journalism. (August 2016) - Fisher, Caroline
The goal of advocacy is commonly used to distinguish journalism from public relations practice. At the same time, there is a strong tradition of advocacy reporting in journalism that weakens this point of distinction. In an attempt to reconcile this apparent contradiction, this article draws on the concept of a continuum to explain extremes in journalism practice and 'contingency theory' in public relations, which posits a range of variables can influence the degree of advocacy adopted by public relations practitioners when dealing with an organization's target publics. This article contends that the degree and type of advocacy present in journalism is also dependent on a range of macro, organizational, journalism production, source and personal factors. It argues that each work of journalism falls along a continuum of advocacy, ranging from subtle displays at one end to overt at the other, where some stories might be hard to distinguish from public relations.